1995
DOI: 10.1074/jbc.270.34.19729
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutagenesis of Arginine 72 of HIV-1 Reverse Transcriptase

Abstract: In order to determine the catalytic role of Arg72 of HIV-1 reverse transcriptase (RT), we carried out site-directed mutagenesis at codon 72. Two mutant proteins (R72A and R72K) were purified and characterized. With Arg to Ala substitution the kcat of the polymerase reaction was reduced by nearly 100-fold with poly(rA) template, but only about 5-15-fold with poly(rC) and poly(dC) templates. The Arg to Lys substitution exhibited a qualitatively similar pattern, although the overall reduction in kcat was less sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
63
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 36 publications
17
63
2
Order By: Relevance
“…In some of our assays, k pol is increased more than 150-fold, for example when BH 3 -3TCTP is used instead of the unsubstituted 3TCTP. An efficient incorporation of BH 3 -TTP is even achieved using the R72A substitution, which decreases the polymerase activity ϳ100-fold (15,31,34,35). Hence, these enzymatic results highlight the general potential given by BH 3 derivatives to circumvent resistance brought by almost any discrimination-associated mutation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In some of our assays, k pol is increased more than 150-fold, for example when BH 3 -3TCTP is used instead of the unsubstituted 3TCTP. An efficient incorporation of BH 3 -TTP is even achieved using the R72A substitution, which decreases the polymerase activity ϳ100-fold (15,31,34,35). Hence, these enzymatic results highlight the general potential given by BH 3 derivatives to circumvent resistance brought by almost any discrimination-associated mutation.…”
Section: Discussionmentioning
confidence: 78%
“…It was thus of interest to know whether other substitutions or other catalytically critical amino acid residues would also be turned into catalytically irrelevant amino acids by the ␣-boranophosphate group. Arg 72 is such an amino acid, as its mutation to alanine nearly abrogates polymerase activity (31). Lys 65 is in the vicinity of the ␤-and ␥-phosphates of the incoming nucleotide, and K65R-mediated drug resistance is suppressed by the BH 3 substitution.…”
Section: The Role Of the Bh 3 Group In The Suppression Of Drugmentioning
confidence: 99%
“…Residue Ala 114 also interacts with the dNTP ␤-phosphate in the RT⅐T/P⅐dNTP ternary complex (20). Some studies have suggested that mutagenesis of RT residues interacting with the dNTP phosphates may directly affect RT pyrophosphorolytic activity (21,22). 2 In addition to the A114S mutation, a number of other resistance mutations appear to resensitize AZT-resistant HIV-1 to AZT.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations introduced by site-directed mutagenesis at codons 72, 89, 90, 113, 114, 115, 151, 154, 183, and 190 in RT were shown to decrease sensitivity to foscarnet (17,26,27,29,39,42,49).…”
mentioning
confidence: 99%